2017
DOI: 10.1038/nature20794
|View full text |Cite
|
Sign up to set email alerts
|

Integration of temporal and spatial patterning generates neural diversity

Abstract: Summary In the Drosophila optic lobes, 800 retinotopically organized columns in the medulla act as functional units for processing visual information. The medulla contains over 80 types of neurons, which belong to two classes: uni-columnar neurons have a stoichiometry of one per column, while multi-columnar neurons contact multiple columns. We show that combinatorial inputs from temporal and spatial axes generate this neuronal diversity: All neuroblasts switch fates over time to produce different neurons. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
158
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 132 publications
(179 citation statements)
references
References 49 publications
(64 reference statements)
6
158
2
Order By: Relevance
“…In theory, these mechanisms could explain how at least 20 neuronal types are produced by each neuroblast (Figure 1 d ). Additional mechanisms were required to explain the full diversity of medulla cell types observed (approximately 80), and another recent study (31) has found that some of this additional diversity stems from reginal identity.…”
Section: Development: Generation Of Cell-type Diversitymentioning
confidence: 99%
See 4 more Smart Citations
“…In theory, these mechanisms could explain how at least 20 neuronal types are produced by each neuroblast (Figure 1 d ). Additional mechanisms were required to explain the full diversity of medulla cell types observed (approximately 80), and another recent study (31) has found that some of this additional diversity stems from reginal identity.…”
Section: Development: Generation Of Cell-type Diversitymentioning
confidence: 99%
“…The production of additional cell-type diversity in the medulla takes advantage of regionalized positional information (31). Although all neuroblasts in the OPC progress through the same temporal series, spatially distributed factors modify the types of neurons that are produced in each of at least eight distinct regions along the crescent (Figure 1 e ).…”
Section: Development: Generation Of Cell-type Diversitymentioning
confidence: 99%
See 3 more Smart Citations